Closure study on optical and microphysical properties of a mixed urban and Arctic haze air mass observed with Raman lidar and Sun photometer - Mueller, D.; Mattis, I.; Ansmann, A.; Wehner, B.; Althausen, D.; Wandinger, U.; Dubovik, O. (Journal of Geophysical Research: Atmospheres, 2004)
[1] We present a comprehensive optical and microphysical characterization of an intense haze event observed over Leipzig ( 51.3 degreesN, 12.4 degreesE), Germany, in April 2002. This event was characterized by unusually high optical depths. The haze consisted of a mixture of urban and Arctic haze aerosols which were advected from the Arctic regions across eastern Europe and Scandinavia. For the first time a closure study on such an event could be carried out on the basis of combined observations with Raman lidar and Sun photometer. This study also served as a performance test of the inversion algorithms that are used for retrieving microphysical particle properties from the optical data sets. A comparison of parameters derived in this study to respective quantities determined in the Arctic regions showed that Arctic-haze-like material dominated the optical and microphysical particle properties, although a significant amount of this haze must have consisted of urban aerosols. The urban aerosols from eastern Europe had properties rather similar to those characteristic for the well-aged particles of Arctic haze. The major part of the haze was confined to heights below 3 km. Optical depth was 0.4 - 0.5 at 532 nm on 8 April 2002. The particle backscatter-to-extinction ( lidar) ratio varied between 35 and 75 sr at 355 and 532 nm. The Angstrom exponent of particle extinction in the wavelength range from 355 to 532 nm was 1.8 - 2.8. The inversion of the lidar optical data resulted in particle effective radii around 0.19 +/- 0.04 mum, volume concentrations of 16 - 33 mum(3) cm(-3), surface area concentrations of 270 - 510 mum(2) cm(-3), and a single-scattering albedo around 0.97 +/- 0.06 at 532 nm. Particle size distributions showed a rather pronounced monomodal structure in the accumulation mode, which is characteristic for well-aged particles. The particle properties derived from the two instruments agreed well for intensive parameters, i.e., Angstrom exponents, lidar ratio, effective radius, and single-scattering ...